2017
DOI: 10.1167/iovs.16-20204
|View full text |Cite
|
Sign up to set email alerts
|

β2–Adrenergic Receptor Antagonism Attenuates CNV Through Inhibition of VEGF and IL-6 Expression

Abstract: PurposeThe role of β–adrenergic receptor (AR) signaling in neovascular ocular diseases has recently emerged. We have previously reported that intraperitoneal propranolol inhibits choroidal neovascularization (CNV) in vivo and β2-AR blockade reduces vascular endothelial growth factor (VEGF) expression in mouse retinal pigment epithelium and choroidal endothelial cells in culture. Here we tested the hypothesis that the β2-AR regulates CNV through modulation of VEGF and inflammatory cytokine expression.MethodsMic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 46 publications
2
33
0
1
Order By: Relevance
“…VEGF, a specific mitogen for endothelial cells, has been identified as a key mediator in the retina and CNV [4]. A number of studies have observed that retinal pigment epithelial (RPE) cell-derived VEGF plays a key role in the progression of CNV [5-7]. VEGF is also increased in the vitreous and CNV membranes of patients with AMD [6, 8].…”
Section: Introductionmentioning
confidence: 99%
“…VEGF, a specific mitogen for endothelial cells, has been identified as a key mediator in the retina and CNV [4]. A number of studies have observed that retinal pigment epithelial (RPE) cell-derived VEGF plays a key role in the progression of CNV [5-7]. VEGF is also increased in the vitreous and CNV membranes of patients with AMD [6, 8].…”
Section: Introductionmentioning
confidence: 99%
“…14 The present work demonstrates, for the first time, the modulatory effect of propranolol on the angiogenic activity of MPs in a choroidal explant model; suppression of PEDF action was sufficient to abrogate antineovascular effects of propranolol in choroidal explant. These findings uncover an additional element of complementarity related to actions of propranolol in CNV by acting not only on RPE, choroidal pericytes, and endothelium, 9 but also on invading MPs.…”
Section: Discussionmentioning
confidence: 79%
“…1A-C), consistent with previous reports. 9 The effect of propranolol was associated with reduced IL-6 and TNF expression ( Fig. 1E), both of which promote cell proliferation, [28][29][30] respectively, through the MAPK cascade 31,32 and through augmentation of VEGF transcription.…”
Section: Propranolol Limits Cnv While Increasing Infiltration Of Inflmentioning
confidence: 99%
See 2 more Smart Citations